Documents : 29.08. – 09.11.25 - Koester, Joachim (Fotografisk center, 2025)
Group exhibition. The exhibition will present works by Danish and international artists who in a variety of ways use photography or other camera-based media in their practice to investigate, illuminate, contest or challenge photography's status as document, truth or evidence - materially as well as thematically and culturally.